Undifferentiated Carcinoma With Osteoclastic Giant Cells of the Pancreas Clinicopathologic Analysis of 38 Cases Highlights a More Protracted Clinical Course Than Currently Appreciated - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
Undifferentiated carcinomas with osteoclastic giant cells of the pancreas (OGC) are rare tumors. The current impression in the literature is that they are highly aggressive tumors similar in prognosis to ductal adenocarcinomas. In this study, the clinicopathologic characteristics of 38 resected OGCs were investigated and contrasted with 725 resected pancreatic ductal adenocarcinomas without osteoclastic cells (PDCs). The frequency among systematically reviewed pancreatic cancers was 1.4%. OGCs showed a slight female predominance (62.9%, vs. 51.4% in PDCs). The mean age was 57.9 years (vs. 65.0). The mean size of invasive cancer was 5.3 cm (vs. 3.2). They were characterized by nodular, pushing-border growth, and 8 arose in tumoral intraepithelial neoplasms (4 in mucinous cystic neoplasms, 4 in intraductal papillary mucinous neoplasms type lesions), and 23 (61%) also showed prominent intraductal/intracystic growth. Twenty-nine (76%) had an invasive ductal/tubular adenocarcinoma component. Osteoid was seen in 12. Despite their larger size, perineural invasion and nodal metastasis were uncommon (31.6% and 22.6%, vs. 85.5% and 64.0%, respectively). Immunohistochemistry performed on 24 cases revealed that osteoclastic cells expressed the histiocytic marker CD68, and background spindle cells and pleomorphic/giant carcinoma cells often showed p53 and often lacked cytokeratin. Survival of OGCs was significantly better than that of PDCs (5 yr, 59.1% vs. 15.7%, respectively, P=0.0009). In conclusion, pancreatic OGCs present with larger tumor size and in slightly younger patients than PDC, 21% arise in mucinous cystic neoplasms/intraductal papillary mucinous neoplasms, and 61% show intraductal/intracystic polypoid growth. OGCs have a significantly better prognosis than is currently believed in the literature.
Keywords: undifferentiated; osteoclast; pancreas; intraductal; sarcomatoid carcinoma; TUMOR-INFILTRATING NEUTROPHILS; DUCTAL ADENOCARCINOMA; CLASSIFICATION-SYSTEM; ONCOGENE MUTATIONS; CANCER-PATIENTS; ORIGIN; HISTOGENESIS; ASSOCIATION; PROGNOSIS; NEOPLASMS